Profesionalisme Tenaga Rekam Medis Ditinjau dari Beban Kerja dan Efisiensi Waktu di Puskesmas Cempae - Hidayat Asikin; Andi Nur Arifah Apriani Azis; Suarni Suarni; Hasyati Hasyati (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Professionalism of medical record officers plays a strategic role in supporting the quality of primary health care services. Increasing administrative workload and the implementation of electronic medical records require not only formal qualifications but also effective time management and service quality. This study aimed to analyze the relationship between education level, training program, service quality, workload, and time efficiency with the professionalism of medical record administrative officers at Puskesmas Cempae. This study is a secondary analysis of data collected in 2009 at the medical record administrative unit of Puskesmas Cempae and re-analyzed in 2024 to assess its relevance within the current primary health care policy context. A total of 19 officers were included using total sampling. Data were collected using a structured questionnaire that had passed validity and reliability testing. Data were analyzed using Fisher’s Exact Test with a 95% confidence level (α = 0.05). The findings showed that education level (p = 0.003), service quality (p = 0.008), and time efficiency (p = 0.023) were significantly associated with professionalism, while training programs did not show a statistically significant relationship (p = 0.057). Professionalism of medical record officers is influenced by formal education, quality of service delivery, and effective time management. Strengthening continuous education and operationally relevant training is essential to improve professionalism in primary healthcare administration.